INTENSITAS MOTIVASI BERPRESTASI MELALUI PEMBELAJARAN DARING - Rizki Akmalia (PIONIR: JURNAL PENDIDIKAN, 2021)
In the 21st century, Indonesia is that the spread of learning is done boldly considering the cases of covid-19 in Indonesia are increasing day by day. The policy concerns educational institutions at the central and regional levels. This policy is considered to be an effective solution so that they do not interact with each other, even just using various media. In the current era, it is evident that the learning system seems to have changed, from what children used to feel in a (traditional) classroom atmosphere to learning that is rigid and monotonous in front of the screen. By implementing the bold learning system or learning from home (BDR), students are required to have facilities that can support these activities starting from smartphones, networks and data packages. Interestingly, in the midst of this epidemic, it has had an impact on all aspects of life, especially in education starting from an early age to higher education. The impact of this bold learning is numerous. Many students do not have smartphones to study boldly and schools cannot provide such facilities for low economic conditions. Not only that, parents who have time difficulties in controlling their children's learning at home will cause children to be lazy to study and of course achievement will decrease. So in this case, the role of parents is the main key in children's learning so that children's interest in learning and achievement does not decrease even though the learning process is not direct with face to face.